Creating and enacting culturally responsive assessment for First Nations students in higher education settings - Steele, Carly; Gower, Graeme; Bogachenko, Tetiana (SAGE, 2024)
In this article, we argue that current assessment practices in higher education require urgent examination and should be re-imagined in culturally responsive ways to ensure fairness for all. From sociocultural and social justice perspectives, we highlight examples of cultural and linguistic bias in assessment that disadvantages many First Nations students. Incorporating a constructivist viewpoint, we argue that assessment practices must keep pace with culturally responsive pedagogical practices to improve assessment validity for First Nations students and to maintain constructive alignment between learning, teaching, and assessment. Based on qualitative interviews with stakeholders in the On Country Teacher Education program, we describe how university lecturers changed their approaches to assessment and modified their assessment tasks to enact and create culturally responsive assessments. These practices, whilst beneficial for First Nations students, are viewed as being ‘responsive’ rather than ‘proactive’. Recommendations include shifting to a ‘proactive’ stance by evaluating the validity of student learning outcomes and assessment design from the onset.